Tinjauan Hukum Islam terhadap Persaingan Usaha Beda Harga pada Toko Sembako Pasar Panorama Lembang - Rima Karnipa Agusti; Popon Srisusilawati; Akhmad Yusup (UNISBA Press, 2023)
Abstract. Trade is a basic form of human economic activity with the aim of achieving profits through buying and selling. Broadly speaking, business is often interpreted as a whole business activity that is carried out by a person or entity on a regular and continuous basis, namely in the form of activities of providing goods or services or facilities to be traded, exchanged or leased with the aim of making a profit. Islam Talking about business competition, in Islam every human being is encouraged to take action in trying but Islam underlines that the business in question should be in goodness not the other way around which can plunge people into evil deeds. This study uses qualitative research methods with a case study approach, data collection techniques, observation, interviews, and literature study. The result of his research is that as long as there is no argument against the creation of a muamalah type, then muamalah is permissible (mubah). In relation to habl min an-nas (muamalah), its implementation is left to humans according to conditions at all times not contrary to religious principles. For sellers, it is better if the price difference given in the price difference for buying and selling groceries is minimized again in nominal terms to close to the minimum and always maintain good quality groceries for buyers, so that buyers are more satisfied in shopping for groceries, try to always ask about the price of groceries because the price of groceries can be change from time to time depending on conditions and season, and the quality of the groceries to be purchased. Abstrak. Bisnis adalah bentuk utama dari kegiatan ekonomi manusia, yang tujuannya adalah untuk mendapatkan keuntungan melalui jual beli. Secara umum, bisnis sering diartikan sebagai totalitas dari apa yang dilakukan seseorang atau organisasi secara teratur dan berkesinambungan. Setiap makhluk sosial disarankan untuk bersaing menurut Islam, tetapi dalam islam di tekankan bahwa bisnis disini harus didasarkan pada perbuatan baik. Tujuan dari penelitian ini untuk mengetahui faktor-faktor serta menganalisis tinjauan hukum Islam terhadap persaingan usaha beda harga pada toko sembako di Pasar Panorama Lembang. Metode penelitian yang digunakan yaitu kualitatif dengan pendekatan studi kasus, teknik pengumpulan data observasi, wawancara, dan studi pustaka. Hasil dari penelitian ini yaitu muamalah boleh (mubah) selama tidak ada dalil yang melarang pembuatan jenis muamalah ini. Mengenai ‘habl min an-nas’, penerapannya diserahkan kepada manusia dengan syarat-syarat tertentu sepanjang tidak melanggar prinsip-prinsip agama. Bagi para penjual, selisih harga antara jual beli sembako sebaiknya dijaga seminimal mungkin dan dijaga pada nilai nominal yang tinggi. Hal tersebut bertujuan agar pembeli lebih puas saat berbelanja sembako, dan bagi para pembeli diusahakan untuk selalu menanyakan harga sembako karena harga sembako sewaktu-waktu dapat berubah berdasarkan musim, kondisi dan kualitas sembako.